Performance analysis of Navigation AI on Commercial Game Engine: Autodesk Stingray and Unity3D - Moch Fachri; Ali Khumaidi; Nur Hikmah; Nuke L Chusna (Jurnal Mantik, 2020)
This research establish crowd simulation on modern game engine such as Autodesk Stingray and Unity 3D. This paper explores the navigation system of both game engine. Furthermore we compare the navigation performance for each navigation system used by those engine: The gameware Navigation which is used in Stingray as its middleware for navigation AI, and Unity Navigation used in Unity3D. We simulate the crowd simulation using scenario of crossroad and narrow-passage. Experimental result demonstrates the navigation of hundreds of agents in densely populated environments.